A multi-analytical study of the fifteenth century mural paintings of the Batalha Monastery (Portugal) in view of their conservation - Valadas, Sara (2014)
The systematic characterization of the painting’s palette and technique applied on the execution of the mural paintings of the Batalha Monastery (Batalha, Leiria, Portugal) is presented. These are the oldest mural paintings known in Portugal (apart from Roman frescoes) and represent the beginning of an artistic Portuguese tradition that continues until the nineteenth century. The aim of the study was to identify for the first time by adopting a multi-analytical physico-chemical approach of the pigments, binder, and alteration products (white veils, crusts, and pigment alteration) of these unique works of arts in order not only to better understand the painting technique, but also to support a conservation-restoration intervention that took place from April to August 2010.